FINANCIAL PERFORMANCE AND ESG SCORES IN MINING-INDUSTRIAL FIRMS DURING COVID-19 - Diky Paramitha; Etik Ipda Riyani; Kan Wen Huey (INSTITUT TEKNOLOGI DAN BISNIS PGRI DEWANTARA JOMBANG, 2026)
Introduction: Environmental, Social, and Governance (ESG) performance gained prominence during COVID-19, yet whether internal financial fundamentals shape sustainability commitments remains debated. This study examines ESG scores as a function of profitability (ROA), solvency (DER), and liquidity (CR) in crisis conditions. Methods: Using panel data from 10 mining and industrial firms listed on the Indonesia Stock Exchange during 2020–2021, this study applies Random Effect Model regression with dummy and interaction terms to capture sectoral differences. Results:ROA, DER, and CR have no significant simultaneous or partial effect on ESG scores (Adj. R² = 13.48%). Liquidity shows the strongest positive association. Profitability exhibits a weak positive tendency in mining but weak negative in industrial firms, though differences are statistically insignificant. Discussion: ESG commitments during the pandemic were not driven by financial performance, suggesting stronger influence from external pressures and non-financial factors. Sector-specific contexts should inform future ESG strategies.